Team sport performance following eastward and westward long-haul air travel - Duffield, R.; Fowler, P. M.; Crowcroft, S.; Mendham, A.; Halson, S.; Vaile, J. (20th Annual Congress of the European College of Sport Science (ECSS), 24th-27th June 2015, Malmö -Sweden. Book of Abstracts, 2015)
Introduction: Though international travel is a requirement for elite team-sport athletes, limited information is available on the post-travel recovery timeline1. Moreover, whilst it is proposed that jet-lag symptoms are worse following eastward compared to westward long-haul air travel2, this is yet to be confirmed from relevant physical performance measures. Consequently, the present study determined the effects of eastward and westward long-haul air travel on physical performance relevant to team-sports.